EFFORTS TO INCREASE REPURCHASE INTENTION THROUGH THE IMPLEMENTATION OF DIGITAL MARKETING PROMOTION FOR DIMSUM S&D SNACK SME PRODUCTS IN MEDAN CITY - Pane, Dewi Nurmasari; Fikri, Miftah El (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
This research aims to enable S&D snack owners who are engaged in dimsum producers on a home production scale to increase their sales through the implementation of digital marketing-based promotions. The main problem in this research is the lack of understanding of home-scale industry owners in promoting through digital marketing. The research method used is descriptive qualitative. The results of the analysis and identification are expected to increase the ability of SMEs to carry out promotions through digital marketing so as to increase repurchase intention, especially dimsum products from S&D Snack.